Tameness does not correlate with the learning of an appetitive association in a wild canid. Issue 1 (8th March 2018) - Petelle, Matthew B; Périquet, Stéphanie; le Roux, Aliza
Abstract: Individual differences in cognition have been shown to be common in some animal taxa, and recent evidence suggests that an individual's personality can be associated with an individual's cognitive strategy. We tested whether wild bat-eared foxes Otocyon megalotis differ in a risk-taking behavior (tameness) and whether this trait correlated with appetitive association learning performance. While our result shows that individuals differed in their tameness, we found no association between this personality trait and learning the appetitive association. This result does not support the framework that differences in cognition are associated with differences in personality; however, our small sample size does not allow us to assert that personality cannot be associated with cognition in this system. This study highlights that measuring cognition and personality in wild systems presents added difficulty and that correlations found in captive animals may not be evident in their wild counterparts.